Interplay between Structure and Dynamics in Chitosan Films Investigated with Solid-State NMR, Dynamic Mechanical Analysis, and X-ray Diffraction (2011)
ABSTRACT: Modern solid-state NMR techniques, combined with X-ray diffraction, revealed the molecular origin of the difference in mechanical properties of self-associated chitosan films. Films cast from acidic aqueous solutions were compared before and after neutralization, and the role of the counterion (acetate vs Cl) was investigated. There is a competition between local structure and long-range order. Hydrogen bonding gives good mechanical strength to neutralized films, which lack long-range organization. The long-range structure is better defined in films cast from acidic solutions in which strong electrostatic interactions cause rotational distortion around the chitosan chains. Plasticization by acetate counterions enhances long-range molecular organization and film flexibility. In contrast, Cl counterions act as a defect and impair the long-range organization by immobilizing hydration water. Molecular motion and proton exchange are restricted , resulting in brittled films despite the high moisture content.